The use of social media and its relationship to national identity among university students - Al-Saify, Hassan; Ibrahim, Baneen; Alahmari, Abdullah; Darwish, Shaimaa (Edelweiss Applied Science and Technology, 2024)
This study investigates the relationship between social media engagement and the formation of national identity among university students in the Kingdom of Saudi Arabia (KSA), with a specific focus on the student population. Through an exploration of the extent of social media use, underlying motivations, and their impact on various dimensions of national identity, this research provides valuable insights into the perceptions and sense of belonging of young individuals in the digital era. We conducted a descriptive and analytical survey, administering a questionnaire to a sample of 386 KSA university students to ensure the generalizability of the findings within the student population. The study reveals a noteworthy level of social media engagement among KSA university students, driven by diverse motives encompassing cognitive, social, recreational, and educational aspects. Furthermore, it highlights the positive influence of social media on the students' national identity, with statistically significant correlations observed across cultural, emotional, social, and affiliative dimensions. The findings indicate that KSA university students exhibit a sense of pride in Saudi history and traditions, demonstrate respect for national symbols, and possess a stronger sense of national affiliation, potentially influenced by their online engagement. Based on these findings, the study recommends the strategic utilization of social media platforms to enhance support among KSA university students and Saudi youth in general, particularly for matters pertaining to national issues. By actively promoting national values, preserving cultural heritage, and cultivating a sense of belonging through social media, institutions can effectively strengthen the national identity of the younger generation.